2017
DOI: 10.1080/02770903.2017.1290104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of exhaled breath temperature (EBT) as a marker and predictor of asthma exacerbation in children and adolescents

Abstract: We suggest that EBT may serve as marker and predictor of asthma exacerbation in children. EBT follow-up may be useful in asthma monitoring in children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Previous studies demonstrated that in asthma EBT is related to the degree of airway inflammation [ 47 ], it increases in uncontrolled asthma and decreases in response to anti-inflammatory treatment [ 48 , 50 ], it is significantly higher in patients with severe asthma compared to those with mild to moderate asthma [ 51 ] and it reflects changes in airway inflammation in children with virus-induced asthma exacerbations [ 52 ]. In contrast, other studies found no relationship between EBT and measures of asthma control [ 53 ].…”
Section: Exhaled Breath Temperature (Ebt)mentioning
confidence: 99%
“…Previous studies demonstrated that in asthma EBT is related to the degree of airway inflammation [ 47 ], it increases in uncontrolled asthma and decreases in response to anti-inflammatory treatment [ 48 , 50 ], it is significantly higher in patients with severe asthma compared to those with mild to moderate asthma [ 51 ] and it reflects changes in airway inflammation in children with virus-induced asthma exacerbations [ 52 ]. In contrast, other studies found no relationship between EBT and measures of asthma control [ 53 ].…”
Section: Exhaled Breath Temperature (Ebt)mentioning
confidence: 99%
“…This is the first study to sequentially measure the EBT at three distinct stages, namely the onset of an asthma attack, during the recovery period, and after patients achieved a stable state; the present study is also the first to compare subjects' symptomatology and pulmonary function during these same three time periods. [34][35][36] In conclusion, this study showed that the EBT can be used to assess a pediatric patient's recovery from an asthma attack. Therefore, children with asthma attacks should be encouraged to use exhaled breath thermometers to clinically aid in the maintenance of asthma control and in therapeutic management.…”
Section: Discussionmentioning
confidence: 86%
“…The main strength of our study was that it longitudinally measured the PLET in children who experienced asthma attacks from their initial admission until 1 month after discharge. This is the first study to sequentially measure the EBT at three distinct stages, namely the onset of an asthma attack, during the recovery period, and after patients achieved a stable state; the present study is also the first to compare subjects’ symptomatology and pulmonary function during these same three time periods …”
Section: Discussionmentioning
confidence: 91%
“…The hydrogel sensor was installed on a smooth platform and kept at a distance of 5 cm to record the change in sensor resistance as the hydrogel was exhaled. When the room temperature is 19-25°C and the humidity is 30%-60%, the temperature of the exhaled gas is about 32.3°C, which is higher than the surface temperature of the gel [32]. As shown in Fig.…”
Section: Science China Materialsmentioning
confidence: 88%